Effectiveness of Virtual Reality Technology in Occupational Safety and Health Training - Nik Hasnaa Nik Mahmood; Nurshamshida Md Shamsudin; Mazanah Muhamad; Nor Aida Maskor (Adult Education Research Conference, 2023)
The major reason for incompetent hazard identification by safety personnel is due to ineffective training of hazard identification. Hence, this study aims to examine the effectiveness of Occupational Safety and Health training using Hazard Identification Virtual Reality Simulation
Keywords: Virtual Reality; Virtual Reality Simulation; OSH Training; Training Effectiveness